Status gizi pada siswi remaja di pondok pesantren modern - Mira Dian Naufalina; Hafidhotun Nabawiyah; Dianti Desita Sari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Nutritional status of female students in Modern Islamic boarding schoolBackground: Female students in Islamic Boarding schools whose adolescents, in the majority, need attention because of their physiological condition in the future. Similar studies in Indonesia with significant subjects of adolescent girl students still need to be expanded. Objective: We aim to find out the prevalence of the nutritional status of adolescent girl students in Islamic Boarding Schools. Methods: The study used a cross-sectional design and had 435 respondents from grades 1-6 (11-19 years old) in Darussalam Gontor Modern Islamic Boarding School for Girls 1. The study measured anthropometrics such as weight, height, and middle-upper arm circumference (MUAC). The following variable was nutritional status which is classified based on Body Mass Index-for-age (BAZ) and height-for-age (HAZ) Z-score, as well as chronic energy deficiency (CED) status. Results: Most subjects (77%) were classified as having normal nutritional status based on BMI-for-age. However, there were 47.6% of students experienced CED, and 15.2% of students were stunted based on height-for-age. Nutritional status according to BMI-for-age showed that 72.73% of students with normal nutritional status and 22.75% of students with overweight were found to be stunted. Notably, among the students with normal nutritional status based on BMI-for-age, the majority were also found to have CED (95.65%). Conclusion: The prevalence of adolescent female students with underweight and severe underweight nutritional status based on BMI-for-age was 1.84%, whereas the prevalence of overweight and obesity was 20.92%. Additionally, 47.6% of female students experience CED, and 15.2% are classified as stunting based on height-for-age.